Law Enforcement Against Perpetrators of Pedophilia Crimes in the Indonesia Legal System - Manalu, Mogang M.H.; Saragih, Yasmirah Mandasari; Zarzani, T. Riza (PT FORMOSA CENDEKIA GLOBAL, 2024)
Despite existing regulations concerning sexual violence against children, the reality shows that crimes of sexual violence towards children continue to rise. The method used in this study is normative law with an approach to statutory regulations and case studies. Laws No. 35/2014 and No. 1/2016 establish severe punishments for pedophilia offenders. There has been a significant increase in cases of sexual violence against children, highlighting the need for legal reform that aligns with societal values and emphasizes prevention through education and improved welfare. Child protection must include broad social support, with a multifaceted approach to the factors causing pedophilia and strengthening social control. Effective policies must integrate prevention, support, and capacity building for the future development of child victims, creating a safer environment and supporting the recovery of children.